DST (Digital Storytelling) To Familiarize ‘Stop Bullying’ Cases Among Elementary School Aged-Children - Husna Maulida; Dewi Puspitasari; Norma Nofiyanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2018)
This article discusses about the use of DST as a way to introduce them to the concept of bullying cases among students. As a participatory action research, this research aims to educate students as young learners to aspect of bullying. The term of DST has been increasingly used by scholars to illustrate various forms of support of learning to help young learners learn successfully.